2011
DOI: 10.2174/138161211798764898
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidative Modification in the Aging Organism and the Role of the Ubiquitin Proteasomal System

Abstract: Living in an oxygen containing environment is automatically connected to oxidative stress. Beside lipids and nucleic acids, especially proteins are very susceptible for oxidative modifications. These oxidative modifications comprise alterations of single amino acids, like the formation of protein carbonyls and methionine sulfoxide, or the aggregation of whole proteins. Due to the ongoing accumulation of protein aggregates during the aging process, the cellular protein quality control system becomes more and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 0 publications
3
42
1
1
Order By: Relevance
“…Previous work correlates high levels of protein carbonyls indicating pro-oxidant pathology to Alzheimer's disease, rheumatoid arthritis, diabetes, sepsis, and trauma as well as many other conditions (Tetik et al 2010;Toda et al 2010;Kastle and Grune 2011). Their measurement is straightforward and thus analytically advantageous over many other biomarkers.…”
Section: Protein Carbonylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work correlates high levels of protein carbonyls indicating pro-oxidant pathology to Alzheimer's disease, rheumatoid arthritis, diabetes, sepsis, and trauma as well as many other conditions (Tetik et al 2010;Toda et al 2010;Kastle and Grune 2011). Their measurement is straightforward and thus analytically advantageous over many other biomarkers.…”
Section: Protein Carbonylsmentioning
confidence: 99%
“…Protein cleavage through the alpha-amidation pathway or by oxidation of glutamyl side chains also leads to formation of carbonyl groups at the N-terminal region, where the amino acid is blocked by an alpha-ketoacyl derivative (Kastle and Grune 2011;Mano 2012). This pathway will eventually lead to production of advanced glycation end products (AGEs) by the glycation or glycooxidation reactions formed by secondary reactions of nucleophilic side chains possessing aldehydes or carbonyl derivatives (Kastle and Grune 2011;Mano 2012).…”
Section: Protein Carbonylsmentioning
confidence: 99%
“…Over the last several decades the studies have showed that the progression of neurodegenerative diseases involve the decreased antioxidant levels, impaired mitochondrial activity, increased oxidative damage protein, lipid peroxidation, protein modification, DNA damage and apoptosis [4][5][6][7][8][9] . Oxidative protein modifications occur at a low and persistent level in diverse cells and tissues and accumulate in aging and neurodegenerative diseases [10][11][12][13][14][15][16][17][18][19] . Since no naturally occurring experimental models for neurodegenerative diseases are available, the investigations to explore the disease mechanisms have been done in neurotoxin induced or genetically altered experimental models.…”
Section: Reviewmentioning
confidence: 99%
“…Oxidative stress, which is defined as an imbalance between the pro-oxidant reactive species and antioxidant molecules, both endogenous and exogenous, has been associated with many non-communicable diseases, such as obesity, insulin resistance 10 and diabetes 11 , atherosclerosis 12,13 , autoimmune diseases 14,15 , neurodegenerative diseases 16,17 , chronic renal disease 18,19 , different malignancies 20,21 , as well as in aging 22 as a physiological process.…”
Section: Oxidative Stressmentioning
confidence: 99%